Update on Imaging of Spinal Fixation Hardware - Winegar, Blair A.; Kay, Matthew D.; Chadaz, Tyson S.; Taljanovic, Mihra S.; Hood, Kenneth A.; Hunter, Tim B. (Seminars in Musculoskeletal Radiology, 2019)
This article discusses instrumented spinal surgeries, the radiologic assessment of spinal fixation hardware, and the potential complications of spinal hardware. Radiography is the standard for the postoperative assessment of spinal hardware. Computed tomography and magnetic resonance imaging play a valuable role in the detection of hardware and postsurgical-related complications such as infection, pseudarthrosis, and malpositioned instrumentation. Familiarity with the normal imaging appearance of implanted spinal hardware along with the expected progression of normal postoperative osseous arthrodesis enables recognition of potential complications and helps facilitate appropriate clinical management.
Keywords: spine; instrumentation; hardware; pseudarthrosis; complications